HUBUNGAN HIGIENE SANITASI TERHADAP INFEKSI SOIL TRANSMITTED HELMINTHS PADA MURID SEKOLAH DASAR DI DESA TERONG TAWAH KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - , Rahmawati S.Si, Prof. Dr. Soeyoko, DTM&H ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Soil Transmitted Helminths (STH) infection remain a major problem in Indonesia. The STH infections is related with higiene sanitation.The highest prevalence of the diseases was found in primary school children. Prevalence of worm infection in primary school student in West Lombok is still high. Objective: To determine the relationship between higiene and sanitation and STH infections on primary school students in village Terong Tawah, Labuapi, West Lombok. Methods: The survey was conducted, with cross sectional approach to investigate the relationship between higiene sanitation and STH infections on primary school student in village Terong Tawah, Labuapi District, West Lombok. This research was conducted on 394 students of primary school student, with details of 197 persons on primary school student in village Terong Tawah and 197 persons on elementary school student 44 Ampenan Mataram as a comparison by taking the feces of all respondents and examined using Kato-Katz method. The soil around the house of the respondents examined using MgSO4 floatation method. The results were analyzed using multivariate statistical tests. Results: The results showed the prevalence of STH on primary school student in the village Terong Tawah was 81.7%, while the prevalence of worms in 44 elementary school students Ampenan as a comparison was 12.7%. There was a significant relationship between higiene and sanitation with intestinal worm infection in some following variable: nail cleanliness (p = 0.043 < Î± = 0.05), washing hands (p = 0.000 < Î± = 0.05), the contaminanted soil around the house (p = 0.000 < Î± = 0.05). in 44 primary school student Ampenan obtained the same results is cleanliness nail (p = 0.000 < Î± = 0.05), washing hands (p = 0.000 < Î± = 0.05), the contaminanted soil around the house (p = 0.002 < Î± = 0.05).